Nicotinamide Mononucleotide, an Intermediate of NAD+ Synthesis, Protects the Heart from Ischemia and Reperfusion - Yamamoto, Takanobu; Byun, Jaemin; Zhai, Peiyong; Ikeda, Yoshiyuki; Oka, Shinichi; Sadoshima, Junichi (PLOS ONE, 2014)
Nicotinamide phosphoribosyltransferase (Nampt), the rate-limiting enzyme for nicotinamide adenine dinucleotide (NAD+) synthesis, and Sirt1, an NAD+-dependent histone deacetylase, protect the heart against ischemia/reperfusion (I/R). It remains unknown whether Nampt mediates the protective effect of ischemic preconditioning (IPC), whether nicotinamide mononucleotide (NMN, 500 mg/kg), a product of Nampt in the NAD+ salvage pathway, mimics the effect of IPC, or whether caloric restriction (CR) upregulates Nampt and protects the heart through a Sirt1-dependent mechanism. IPC upregulated Nampt protein, and the protective effect of IPC against ischemia (30 minutes) and reperfusion (24 hours) was attenuated at both early and late phases in Nampt +/− mice, suggesting that Nampt plays an essential role in mediating the protective effect of IPC. In order to mimic the effect of Nampt, NMN was administered by intraperitoneal injection. NMN significantly increased the level of NAD+ in the heart at baseline and prevented a decrease in NAD+ during ischemia. NMN protected the heart from I/R injury when it was applied once 30 minutes before ischemia or 4 times just before and during reperfusion, suggesting that exogenous NMN protects the heart from I/R injury in both ischemic and reperfusion phases. The protective effect of NMN was accompanied by decreases in acetylation of FoxO1, but it was not obvious in Sirt1 KO mice, suggesting that the effect of NMN is mediated through activation of Sirt1. Compared to control diet (90% calories), CR (60% calories for 6 weeks) in mice led to a significant reduction in I/R injury, accompanied by upregulation of Nampt. The protective effect of CR against I/R injury was not significant in cardiac-specific Sirt1 KO mice, suggesting that the protective effect of CR is in part mediated through the Nampt-Sirt1 pathway. In conclusion, exogenous application of NMN and CR protects the heart by both mimicking IPC and activating Sirt1.